The potential habitat of Phlomoides rotata in Tibet was based on an optimized MaxEnt model - Wang, Jun-Wei; Xu, Min; Ngawang, Norbu; Chen, Yonghao; Bonjor, Ngawang; Jia, Xiaoyan; Zeng, Zhefei; Qiong, La (Frontiers in Plant Science, 2025)
IntroductionPhlomoides rotata, an important Tibetan medicinal plant, has garnered significant attention due to its remarkable medicinal value and ecological functions. However, overharvesting and climate change have progressively reduced its distribution range, threatening its survival.MethodsThis study employed an optimized MaxEnt model, integrating field survey data and multiple environmental variables, to predict and analyze the potential suitable distribution of P. rotata in Tibet.ResultsThe model achieved high predictive accuracy, with Ture skill statistic (TSS) = 0.87 and Cohen’s Kappa Coefficient (Kappa) = 0.81. Under current climatic conditions, the suitable habitat area of P. rotata is 33.31×104 km², primarily distributed in alpine meadows and sparse shrublands in regions such as Lhasa, Nyingchi, Qamdo, Shannan, and eastern Nagqu. Analysis of key environmental factors revealed that land cover type (30.7%), temperature seasonality (19.9%), and vegetation type (10.2%) are the most significant drivers influencing the distribution of P. rotata. Under future climate change scenarios, the distribution of suitable habitats exhibits notable dynamic trends. In the low-emission scenario (SSP126), the suitable habitat area shows an overall expansion. In contrast, under medium- and high-emission scenarios (SSP245 and SSP585), the suitable habitat area gradually shrinks. The distribution centers consistently migrate northwestward, with the longest migration distance observed under SSP585 (89.55 km).DiscussionThis study identifies the critical driving factors for the distribution of P. rotata and elucidates its response patterns to climate change. These findings provide a theoretical foundation for the resource management, ecological conservation, and sustainable utilization of Tibetan medicinal plants while offering valuable references for the study of other alpine plants.